KOMUNIKASI INSTRUKSIONAL MAGANG BERSERTIFIKAT (MSIB BATCH 5) MAHASISWA ILMU KOMUNIKASI FIS UNJ - Marisa Puspita Sary; Kinkin Yuliaty Subarsa Putri; Maulina Larasati Putri; Vera Wijayanti Sutjipto; Natasya Ananda Rheta (LPPM Stikosa - AWS, 2024)
This study discusses instructional communication in students of the Communication Science Study Program who participate in the MSIB program. This study uses a qualitative descriptive method whose data collection is carried out through interview techniques. In this study, there were 18 informants who were students of Communication Sciences, Faculty of Social Sciences, Universitas Negeri Jakarta who participated in the batch 5 independent internship program which was carried out for five months. The results of this study showed that the results of the interviews from 18 informants, 16 of whom admitted that communication went well and was responsive with mentors in knowledge transfer. There was also clear and open communication followed by an evaluation so that there was an improvement in the ability recognized by 15 of the 18 informants. In the meaning of MSIB, the 18 informants simultaneously agreed with the MSIB program. This was followed by the use of communication media in the form of Whatsapp by 14 out of 18 informants in communicating something to mentors during the 5th batch of independent internship programs.